Plugs, socket-outlets, vehicle connectors and vehicle inlets. Conductive charging of electric vehicles. Dimensional compatibility and interchangeability requirements for DC pin and contact-tube accessories for Class II or Class III applications Part 4, (29th November 2022) - British Standards Institution,
No abstract available